ELEARNING TEACHERS’ AND STUDENTS’ PERCEPTION TOWARD LIVE-VIDEO CONFERENCE IN AN ELEARNING ENVIRONMENT - Phongsatha, Satha; Cleesuntorn, Athipat (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2017)
In an online learning environment, the majority of teaching and learning are conducted asynchronous communication methods. The tools such as the learning management system, web forum, social media, e-mail, and others are an example of such tools. In order to ensure that students can access to the instructors as well as classmates as in traditional learning method, asynchronous communication means should be included as part of teaching and learning. In modern digital technology, examples of services and software that allow people to communicate synchronously are FaceTime, Skype, LINE, Google Hangout, and others. Not only that people can communicate via voice but they can also see each other as well. Thus, the utilization of video conference software can be a part of teaching and learning in online education. In Thailand, online education degrees is in developing stages and the utilization of the live video conference along with the standard communication mode is getting more well utilized. Thus, it is necessary to investigate the behavior of past usages and the way that the live video conference mode is utilized for online learning in Thailand. This research aims to investigate the nature of usages of the Live Video conference features in order to provide a bigger picture of how the system is being utilized by the students and the teachers so that the method of usages can be further study to ensure the effectiveness of the usages as well as implementation of the system in an online learning environment.